2013
DOI: 10.1016/j.actpsy.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Impaired retention is responsible for temporal order memory deficits in mild cognitive impairment

Abstract: Temporal order memory, or remembering the order of events, is critical for everyday functioning and is difficult for patients with mild cognitive impairment (MCI). It is currently unclear whether these patients have difficulty acquiring and/or retaining such information and whether deficits in these patients are in excess of “normal” age-related declines. Therefore, the current study examined age and disease-related changes in temporal order memory as well as whether memory load played a role in such changes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 53 publications
3
16
0
Order By: Relevance
“…These findings are consonant with the known role of the hippocampus in memory retention and previous research demonstrating that smaller hippocampal volume is associated with worse memory test performance (Arlt et al, 2013;Apostolova et al, 2010;Mungas et al, 2005). They also reinforce previous conclusions that the DMI, relative to the IMI, is more sensitive to memory impairment in those with AD (Duff et al, 2008) as well as our earlier report that MCI patients experience relatively intact encoding but impaired retention (Gillis, Quinn, Phillips, & Hampstead, 2013). The fact that virtually all of the memory subtests (i.e., those occurring after a time delay) were related to hippocampal volumes bilaterally likely reflects the bilateral nature of the presumed disease process (Apostolova et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consonant with the known role of the hippocampus in memory retention and previous research demonstrating that smaller hippocampal volume is associated with worse memory test performance (Arlt et al, 2013;Apostolova et al, 2010;Mungas et al, 2005). They also reinforce previous conclusions that the DMI, relative to the IMI, is more sensitive to memory impairment in those with AD (Duff et al, 2008) as well as our earlier report that MCI patients experience relatively intact encoding but impaired retention (Gillis, Quinn, Phillips, & Hampstead, 2013). The fact that virtually all of the memory subtests (i.e., those occurring after a time delay) were related to hippocampal volumes bilaterally likely reflects the bilateral nature of the presumed disease process (Apostolova et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…A recent study reported that impaired temporal order memory may be a selective behavioral marker of Alzheimer’s disease (Bellassen et al, 2012 ). In addition, temporal order memory deficits have been reported in older adults diagnosed with mild cognitive impairment (Gillis et al, 2013 ), which has been described as a transitional stage between normal aging and Alzheimer’s disease. Therefore, the present findings potentially may have both basic science and clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, retrieving specific information will become especially challenging with the passage of time given the accumulation of pages (digital or physical), notes, or bookmarks. Although patients may be able to locate such information by referencing key events (e.g., holidays), patients with MCI have difficulty retaining the temporal aspects of information (Gillis, Quinn, Phillips, & Hampstead, 2013) and associating information ; for a review see Sperling, 2007); findings that suggest that such temporal or associative referencing will be especially challenging.…”
Section: Common Approachesmentioning
confidence: 99%